Arthur's Fight For Freedom Citizenry Reflected In David Franzoni's King Arthur (2004) : An Individual Psychological Approach - Nugraha, Septian Widhi; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this study is how fight for freedom of Citizenship is reflected in the major characters personality. The aim of this study is to analyze David franzoni's King Arthur based on the structural elements and the development of personality of the major character based on Psychological Approach. This study focuses on the major character, namely Arthur.. This research is qualitative research. The data of the study are text and image taken from two data sources: primary and secondary. The primary data source is the King Arthur movie directed by David franzoni released in 2004. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en scene, cinematography, sound, and editing are related to each other and form a unity. Second, based on the psychologial perspective that the problems of the major character cause the conflict of his psychological condition. It happens when there is contradiction amongs: inferiority feeling, striving for superiority, fictional finalism , style of life, social interest, and creative power. It brings him into the new man with a new psychological views.